Influence of position of panicle on seed and seedling characteristics of rice (Oryza sativa L) - U. R., Sangakkara (Universiti Putra Malaysia Press, 1993)
The characteristics of seeds obtained from primary, secondary and tertiary branches of panicles in four varieties. of Indica rice (Oryza sativa) were evaluated. The germination patterns and viability of procured seed and the vigour and characteristics of seedlings developed from these seeds were also studied. The characteristics of seeds of the three branch types ofthe four varieties and their seedlings were similar. In contrast, marked differences were observed between the seeds obtained from the three types of branches. Seeds of primary branches of the panicle had a greater 100-seed weight. The lowest weight was observed in seeds from tertiary branches. This difference was principally due to the heavier endosperm of the seeds of primary branches, which in turn increased the endosperm:embryo ratios. The viability and germinability ofthe three categories ofseed were similar to those ofseed characteristics. Seed from primary branches of the panicle had a higher viability. The vigour of seedlings from these seeds was also greater. Differences in growth of seedlings from the these seeds was also greater. Differences in growth ofseedlings from the three branches of the rice panicle were similar in terms of characteristics and viability of seeds. The study revealed that seedlings from seeds of primary branches manifested superior growth because of better seed characteristics. Some practical implications of the study are discussed.